Teknik Identifikasi Ektoparasit Pada Ikan Tawes (Barbonymus gonionotus) Yang Di Budidayakan Di Loka Muntilan, Magelang - Deandra Aurel Azeli; Petrus Hary Tjahja Soedibya (Fakultas Perikanan dan Ilmu Kelautan, 2022)
Tawes fish is one of the economically consumed fish that is affordable. In Indonesia, Tawes fish have long been cultivated because they are suitable for tropical climates, so they can be cultivated throughout the year. The purpose of this practical work is to find out how to examine ectoparasites, the types of ectoparasites as well as the intensity and prevalence values carried out at the Muntilan Workshop, Magelang. The stages of examining fish ectoparasites are examined by taking mucus on the surface of the fish's body and cutting a small part of the gill lamellae using scissors. then observed under a microscope with a magnification of 5x, 10x and 40x. The results of the research found six species of ectoparasites in java barb, found were Trichodina sp., Dactylogyrus sp., Gyrodactylus sp., Oodinium sp., Ichtyoptirius sp., dan Myxobolus sp.